Reorientasi Nilai Solidaritas Karang Taruna di Dusun Demen dalam Kegiatan Sinoman di Era Society 5.0 - Aji, Sawaldi Waskito; Karmel, Febronia Lelis; Widiastuti, Anik (Jurnal Ilmu Sosial dan Budaya Indonesia, 2026)
This study aims to examine the reorientation of solidarity values among Karang Taruna in sinoman activities in Dusun Demen in the era of Society 5.0. The background of this research is the shift in youth social interaction patterns due to technological developments which has led to decreased participation in community based activities. This study employs a descriptive qualitative approach conducted in Dusun Demen. The subjects were selected using purposive sampling with three informants consisting of active and inactive members of Karang Taruna who were directly involved in sinoman activities. Data were collected through in depth semi structured interviews and supported by relevant literature. Data analysis was carried out using an interactive model which includes data reduction data display and conclusion drawing. The validity of the data was ensured through source triangulation. The results show that sinoman activities still exist but have experienced changes in the form of participation and the role of youth. Youth involvement tends to decline due to work demands lifestyle changes and the influence of digitalization. Solidarity values have not disappeared but have shifted from collective practices to more personal and situational forms. Therefore a reorientation of solidarity values is needed through the integration of traditional values and the use of technology to remain relevant in the modern era.